The dilemma: scleroderma renal crisis vs lupus nephritis in a patient with mixed connective tissue disorder - Nicola Jackson; Shion Betty; James Appiah-Pippim; Yolin Bueno; Sana Makhdumi (Greater Baltimore Medical Center, 2021)
Introduction Mixed connective tissue disorder (MCTD) is a rare connective tissue disorder characterized by features of systemic lupus erythematosus, dermatomyositis, systemic sclerosis, and rheumatoid arthritis. MCTD is associated with an elevated antibody titer to U1 small nuclear ribonucleoprotein. Case description: A 49-year-old man presented to the emergency department for evaluation of worsening shortness of breath with associated for bilateral hand pain and swelling associated with morning stiffness which was initially thought to be related to systemic lupus erythematous (SLE). He was also found to have a positive autoantibody, and he was later diagnosed with MCTD complicated by scleroderma renal crisis. Conclusion MCTD is a rare connective tissue disorder with overlapping features of SLE, dermatomyositis, systemic sclerosis, and rheumatoid arthritis. The diagnosis of MCTD requires a high index of suspicion and careful workup. Immunosuppressive therapy is the mainstay of treatment that improves patient outcomes.